2020
DOI: 10.1111/petr.13664
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of allogenic hematopoietic cell transplantation for childhood chronic myeloid leukemia: Single‐center experience

Abstract: Background/objectives: Despite the apparent efficacy and favorable toxicity profile of TKIs, allogeneic SCT remains the only curative treatment for CML especially in younger patients, but TRM should be considered. We evaluated the clinical outcomes of pediatric CML patients who had SCT in our center. Methods: This retrospective study included children with CML, who received an allogeneic SCT at Children Cancer Hospital Egypt, 57357, from 2007 to 2017. All patients received myeloablative conditioning chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Comparative HSCT-imatinib analysis in pediatric CML indicated similar 84% (HSCT) and 87% (imatinib) two-year OS and relapse rates [47]. Allogeneic HSCT in pediatric CML showed 97.4% 5-year OS and 79.8% EFS, without mortality at 100 days/1-year post-HSCT [48]. Allogeneic HSCT's chronic-phase CML effectiveness, for TKI failure, reported 84% (adults) and 91% (pediatrics) pooled OS in quantitative synthesis [49].…”
Section: Children and Young Adultsmentioning
confidence: 88%
“…Comparative HSCT-imatinib analysis in pediatric CML indicated similar 84% (HSCT) and 87% (imatinib) two-year OS and relapse rates [47]. Allogeneic HSCT in pediatric CML showed 97.4% 5-year OS and 79.8% EFS, without mortality at 100 days/1-year post-HSCT [48]. Allogeneic HSCT's chronic-phase CML effectiveness, for TKI failure, reported 84% (adults) and 91% (pediatrics) pooled OS in quantitative synthesis [49].…”
Section: Children and Young Adultsmentioning
confidence: 88%
“…Significant benefits in engraftment were observed in MSD bone marrow transplantation [57]. Most studies in CML-CP showed a survival benefit for MSD; the limitation is that those are either retrospective studies and/or were conducted before there were significant improvements in HLA typing, donor search, and treatment of acute graft-versus-host disease (GvHD) [58][59][60]. In addition, these studies have mostly demonstrated a survival advantage for bone marrow as a stem cell source [59,61].…”
Section: Donor and Graft Selectionmentioning
confidence: 99%